SPECIFIC FEATURES OF ELECTROENCEPHALOGRAPHIC PAROXYSMAL ACTIVITY REGISTRATION IN OLD AGE GROUP PATIENTS - S. A. Gulyaev; I. V. Arkhipenko; S. E. Gulyaeva; A. A. Ovchinnikova; A. V. Ovchinnikov (Русский журнал детской неврологии, 2016)
The differential diagnosis of epilepsy and other paroxysmal states mimicking this condition is very important in the daily activity of a neurologist (an epileptologist) since diagnostic accuracy directly ensures the efficacy and safety of treatment. According the data available in the literature, both overdiagnosis of epilepsy (20–25 % of all new diagnosed cases) and its underdiagnosis (as high as 10 %) are frequent diagnostic errors. Such errors are most commonly related to the misinterpretation of electrophysiological evidence in both young patients (in whom paroxysmal phenomena are a result of functional immaturity of brain structures) and elderly patients (in whom paroxysmal activity is a consequence of the development of degenerative processes in the neurons).Objective: to show examples of electroencephalographic (EEG) paroxysmal activity in old age group patients suffering from non-epileptic paroxysms.Now EEG investigation is a highly sensitive technique that requires a physician’s knowledge of neuroanatomy and neurophysiology to correct interpretation of the findings. Non-epileptiform paroxysmal events may be detected not only in children who have immature cerebral cortical neurons and median brainstem structures, but also in the elderly in whom their emergence is due to the development of degenerative processes in the neurons. The similarity of these phenomena with typical EEG epileptiform patterns is not coincidental. The basis for their occurrence is the similar mechanism for glutamate excitotoxicity, but, unlike epilepsy, which is triggered by ischemic and hypoxic processes, rather than by the exhausted reserve abilities of nerve cells during overstimulation. Therefore the detection of this pathological EEG paroxysmal activity calls for careful differential diagnosis.